Behçet's disease in patients of west African and Afro-Caribbean origin. Issue 7 (1st July 2003) - Poon, W; Verity, D H; Larkin, G L; Graham, E M; Stanford, M R
Abstract : Aim: To report the presence of Behçet's disease with ocular involvement in patients of west African or Afro-Caribbean origin. Methods: Case series of eight patients reporting to a tertiary uveitis service. Results: Eight patients with typical features of the disease are presented. Six of the eight patients were tested and found to be HLA-B51 negative. Conclusion: Behçet's disease has only been reported in sporadic case reports in the indigenous west African and Afro-Caribbean populations, in whom the incidence of HLA B51 is also very low. A series of patients from the London region presented with the typical symptoms and signs of disease, most of whom were also HLA B51 negative. The presence of disease in this population, when absent in the indigenous population, suggests either that ascertainment of disease is poor in the indigenous population or that acquired factors may be important in the aetiology of the disease.